Designing Sandwich ELISA with Broadly Reactive Anti-Nucleocapsid Monoclonal Antibodies to Detect Bat-Borne Merbecoviruses - Kong Yen Liew; Yaju Wang; Sneha Sree Mullapudi; Dinah binte Aziz; Wenjie Fan; Min Luo; Paul Anantharajah Tambyah; Yee-Joo Tan (Viruses)
At least three betacoronaviruses have spilled over from bats to humans and caused severe diseases, highlighting the threat of zoonotic transmission. Thus, it is important to enhance surveillance capabilities by developing tools capable of detecting a broad spectrum of bat-borne betacoronaviruses. Three monoclonal antibodies (mAbs) targeting the nucleocapsid (N) protein were generated using recombinant N proteins from severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and Middle East Respiratory Syndrome Coronavirus (MERS-CoV). The cross-reactivities of these mAbs were evaluated against a panel of betacoronaviruses. Sandwich ELISAs (sELISAs) were subsequently developed to detect bat-borne betacoronaviruses that have high zoonotic potential. Among the mAbs, 7A7 demonstrated the broadest cross-reactivity, recognizing betacoronaviruses from the Sarbecovirus, Merbecovirus and Hibecovirus subgenera. The first sELISA, based on mAbs 7A7 and 6G10, successfully detected N protein in all clinical swab samples from COVID-19 patients with cycle threshold (Ct) values < 25, achieving 75% positivity overall (12/16). Using this as a reference, a second sELISA was established by pairing mAb 7A7 with mAb 8E2, which binds to multiple merbecoviruses. This assay detected the N protein of two merbecoviruses, namely the human MERS-CoV and bat-borne HKU5-CoV, at high sensitivity and has a limit of detection (LOD) that is comparable to the first sELISA used successfully to detect COVID-19 infection. These broadly reactive mAbs could be further developed into rapid antigen detection kits for surveillance in high-risk populations with close contact with wild bats to facilitate the early detection of potential zoonotic spillover events.